2009
DOI: 10.1016/j.ecoenv.2008.09.027
|View full text |Cite
|
Sign up to set email alerts
|

Effects of waterborne nano-iron on medaka (Oryzias latipes): Antioxidant enzymatic activity, lipid peroxidation and histopathology

Abstract: a b s t r a c tToxicity tests were performed to investigate possible harmful effects on medaka exposed to nano-iron. Dose-dependent decreases of superoxide dismutase (SOD) and increases of malondialdehyde (MDA) were induced in the medaka embryo, suggesting that oxidative damage was induced by nano-iron. For adult medaka, the disturbance of antioxidative balance was observed during the early exposure period based on the monitoring of the hepatic and cerebral SOD and reduced glutathione (GSH). No terminal oxidat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
94
0
3

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 186 publications
(102 citation statements)
references
References 28 publications
5
94
0
3
Order By: Relevance
“…Due to its high reactive properties, it is most likely that Ag nanoparticles could adhere to the surface of bacteria, followed by reaction with peptidoglycan, then lead to the destruction of cell structure integrity and eventually to cell death (Pal et al 2007;Panacek et al 2006). Due to its highly effective ability to catalyze redox processes, nano-Fe has been widely applied in the degradation of halogenated organic compounds and other persistent toxic substances (Li et al 2009). Oxidative damage and the low cytotoxicity caused by nano-Fe have been reported (Zhou et al 2003;Li et al 2009;Song et al 2009).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to its high reactive properties, it is most likely that Ag nanoparticles could adhere to the surface of bacteria, followed by reaction with peptidoglycan, then lead to the destruction of cell structure integrity and eventually to cell death (Pal et al 2007;Panacek et al 2006). Due to its highly effective ability to catalyze redox processes, nano-Fe has been widely applied in the degradation of halogenated organic compounds and other persistent toxic substances (Li et al 2009). Oxidative damage and the low cytotoxicity caused by nano-Fe have been reported (Zhou et al 2003;Li et al 2009;Song et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Due to its highly effective ability to catalyze redox processes, nano-Fe has been widely applied in the degradation of halogenated organic compounds and other persistent toxic substances (Li et al 2009). Oxidative damage and the low cytotoxicity caused by nano-Fe have been reported (Zhou et al 2003;Li et al 2009;Song et al 2009). Regardless of the synthesis method or particle morphology, Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lipid peroxidation and alterations in antioxidant enzyme activity in embryonic and adult medaka Oryzias latipes exposed to nano-iron was reported by Li et al (2009). Dose-dependent inhibition of SOD activity and increased production of malondialdehyde (MDA) was observed in medaka embryos.…”
Section: Mechanisms Of Metal-induced Oxidative Damagementioning
confidence: 92%
“…Iron has been shown to induce oxidative stress (Sevcikova et al 2011). Li et al (2009) observed lipid peroxidation (LPO) and alterations in antioxidant enzyme activity in embryonic and adult medaka Oryzias latipes exposed to nano-iron. After an iron-enriched diet, LPO was observed in the liver and heart of the African catfish Clarias gariepinus (Baker et al 1997).…”
mentioning
confidence: 99%